Beispiel Nr: 16
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 2x +4y =4\\ -\frac{1}{2}x +3y = 3 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ \text{I nach x auflösen}\\ 2 x +4 y =4 \\ 2 x +4 y =4 \qquad /-4 y\\ 2 x =4 -4 y \qquad /:2 \\ x =2 -2 y \\ \text{I in II}\\ -\frac{1}{2} (2 -2 y ) + 3 y = 3 \\ -1 +1 y +3 y = 3 \qquad / -\left(-1\right) \\ +1 y +3 y = 3 -\left(-1\right) \\ 4 y = 4 \qquad /:4 \\ y = \frac{4}{4} \\ y=1 \\ x =2 -2 y \\ x =2 -2 \cdot 1 \\ x=0 \\ L=\{0/1\} \end{array} & \begin{array}{l} I \qquad 2 x +4 y =4\\ II \qquad -\frac{1}{2} x +3 y = 3 \\ \text{I nach y auflösen}\\ 2 x +4 y =4 \\ 2 x +4 y =4 \qquad /-2 x\\ 4 y =4 -2x \qquad /:4 \\ y =1 -\frac{1}{2}x \\ \text{I in II}\\ -\frac{1}{2}x + 3(1 -\frac{1}{2} x ) = 3 \\ 3 -1\frac{1}{2} x +3 x = 3 \qquad / -3 \\ -1\frac{1}{2} x +3 x = 3 -3 \\ -2 x = 0 \qquad /:\left(-2\right) \\ x = \frac{0}{-2} \\ x=0 \\ y =1 -\frac{1}{2} x \\ y =1 -\frac{1}{2} \cdot 0 \\ y=1 \\ L=\{0/1\} \end{array} \end{array} $